Peran dan Kedudukan Perempuan Dalam Laskar Hizbullah Pada Masa Resolusi Jihad Sebagai Wawasan Sejarah Lokal - Matingvan, Elanda; Hariyono, Hariyono (Kamaya: Jurnal Ilmu Agama, 2024)
The Jihad Resolution period in Indonesia was an event where Muslims agreed to defend Indonesia's independence. At this time, almost all elements of society took part, including women. The role of women during the Jihad Resolution period included supporting Laskar Hezbollah. This role of women cannot be separated from women's organizations, mothers, wives, and other individuals. However, the role of women during this period is less discussed in history, especially through the dimensions of women's femininity itself. Therefore, the purpose of this research is to present the role of women in the perspective of struggle in general and women's historiography through the dimension of femininity. In examining this research, a historical qualitative research type with a historical or historiographic approach is used with data collection methods through interviews and literature studies. So that the results of the research show that women have a role in the front line through the perspective of the struggle at that time, and have a role in the back line through the dimensions of women's femininity that are set aside by the patriarchal culture at that time which views how the act of struggle should be. Women contributed directly or indirectly, consciously, or unconsciously participated in the struggle through the things they could and used to do. Things that women did that were seen as not important, but had a chain effect on Indonesia's independence. And how women's actions are synonymous with gentleness which becomes a strength for them to support fighters who need that side amid the chaos of war. Thus, the role of women became complex in times of war, not only on the front lines and rear lines but in society emotionally, socially, and morally.